Kontribusi Hadis Terhadap Pengembangan Pendidikan Karakter - Ikhsan Kamil; Hidayat Hidayat (EL-EMIR Institute, 2026)
Character education is a crucial aspect in shaping a generation with noble morals amidst the changing times and technological advances that influence student behavior. The moral crisis occurring in communities and schools demonstrates the importance of strengthening character education based on Islamic values. This study aims to determine the contribution of the hadith to the development of character education and to analyze the implementation of hadith values ​​in character formation in students. The study used a qualitative approach with library research. Data were obtained from hadith books, books, journals, and various literature related to character education from an Islamic perspective. Data analysis was conducted using content analysis, examining the meaning of the hadith as it relates to the values ​​of character education. The results indicate that the hadith plays a significant role in the development of character education through the values ​​of honesty, discipline, responsibility, compassion, and tolerance. The implementation of hadith values ​​can be achieved through teacher role models, school practices, and the role of families in shaping students' behavior with noble morals in accordance with Islamic teachings.